Crude Oil and Economic Performance in Nigeria in the Presence of Multicollinearity Using Cobb-Douglass Model - Sunday, Adesina Olumide; Olaoluwa, Agboola O.; Funmi, Adedotun Adedayo; Iyanuoluwa, Adesiyan Gospel (International Journal of Energy Economics and Policy, 2025)
Nigeria’s major source of revenue, energy and foreign exchange is crude oil for over three decades. There is need to identify business activities surrounding crude oil that impact the real gross domestic product of Nigeria. This research project models the impact of crude oil on Nigeria economic growth using non-linear econometric model, namely, Cobb-Douglas production function. Crude oil data was obtained from National Bureau of Statistics covering 1981-2021, exploratory data analysis on Nigeria’s crude oil data and diagnostic tests as multicollinearity and autocorrelation tests were carried out on the data then the data was fitted to Cobb-Douglas production function model. The results showed that real gross domestic product has a positive relationship with crude oil revenue and crude oil consumption. Based on the findings of this project work, it is recommended that the government should implement policies and take steps to preserve and manage the oil sector effectively.